Aberrations in Structured Illumination Microscopy: A Theoretical Analysis - Liu, Xin; Tu, Shijie; Xu, Yan; Song, Hongya; Liu, Wenjie; Liu, Qiulan; Kuang, Cuifang; Liu, Xu; Hao, Xiang (Frontiers in Physics, 2020)
In super-resolution optical microscopes, aberrations often compromise the image performances by reducing its resolution and contrast. In previous works, the aberrations in stimulated emission depletion (STED) microscopy and single-molecule localization microscopy (SMLM) have been well investigated, while the research on the aberrations in structured illumination microscopy (SIM) is not sufficient, the researchers always poured attention into aberrations only in the detection path. In this paper, we investigate the aberrations in SIM in a comprehensive manner, and their causes and effects on both the illumination and the detection paths are discussed. The aberrations in the illumination path may distort illumination patterns, and deteriorate the final images, together with the aberrations in the detection path. In addition, several non-aberration-related factors, especially the misalignment of the incident beams with respect to the objective pupil, can also dramatically influence the performances of SIM. The analysis provides the theoretical basis and reference for optimizing a SIM system.